2023
DOI: 10.1038/s41420-023-01324-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of astragalin via activating PI3K/Akt-mTOR-mediated autophagy on APP/PS1 mice

Abstract: As a small molecule flavonoid, astragalin (AST) has anti-inflammatory, anti-cancer, and anti-oxidation effects. However, the impact and molecular mechanism of AST in Alzheimer’s disease (AD) are still not clear. This study aims to investigate the neuroprotective effect and mechanism of AST on APP/PS1 mice and Aβ25-35-injured HT22 cells. In this study, we found that AST ameliorated cognitive dysfunction, reduced hippocampal neuronal damage and loss, and Aβ pathology in APP/PS1 mice. Subsequently, AST activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…5xFAD is a new type of AD mouse model developed on the basis of APP/PS1 and has received widespread attention. In recent animal studies on AD, APP/PS1 mice was widely used as the AD model due to that they have the characteristics of AD well at the cellular and molecular levels [18][19][20]. We believe that APP/PS1 mice can meet our study.…”
Section: A Animal Preparationmentioning
confidence: 74%
See 1 more Smart Citation
“…5xFAD is a new type of AD mouse model developed on the basis of APP/PS1 and has received widespread attention. In recent animal studies on AD, APP/PS1 mice was widely used as the AD model due to that they have the characteristics of AD well at the cellular and molecular levels [18][19][20]. We believe that APP/PS1 mice can meet our study.…”
Section: A Animal Preparationmentioning
confidence: 74%
“…With the accumulation of gene effects, typical features similar to AD can appear in pathology and learning cognitive abilities, effectively simulating the characteristics of AD. Many scholars have studied the treatment and pathogenesis of AD based on this model mouse, which has high application value [18][19][20]. However, it remains unclear how long-term low-intensity TUS modulates neural activity in the hippocampal brain region, which is closely related to learning and memory, of the APP/PS1 AD mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the underlying mechanisms, we conducted RNA sequencing (RNA-seq) on H/R-treated PRTCs. KEGG analysis indicated that H/R activated autophagy and several well-known signaling pathways, including the hypoxia-related HIF-1 signaling, mTOR activity 24 , and PI3K/AKT 25 and MAPK 26 linked to autophagy regulation (Fig. 5a ).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal autophagy is involved in the development of AD ( Yuan et al, 2022 ). Activation of autophagy alleviates pathological characters and cognitive deficits in APP/PS1 mice ( Yang et al, 2023 ). The MAMs mark the starting point of autophagosome formation.…”
Section: The Role Of Mams In Abnormal Autophagy In Admentioning
confidence: 99%